Fatwa MUI tentang Penyimpangan Ajaran Islam dan Tindakan Pelanggaran Kebebasan Berkeyakinan - Rahmad Ari Wibowo (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This study focuses on the contribution of religious fatwa MUI on the situation of religious life are colored by various types of discrimination, intolerance, and even violence based on religion. This study found that the MUI's religious fatwas, in practice, is used as a foothold by state officials to violate the freedom of religion/belief. Risky, the legal policy is no longer based on the constitution and the law, but the MUI fatwa. These conditions have spawned authoritarian government legitimized by religious views. On the other hand, the fatwa provides religious life situations are colored by different types of discrimination, intolerance, and even violence based on religion.